Agri-environmental diagnostic and rehabilitation in a stretch of a hydrographic basin assessed by remote sensing and water turbidity - Vischi Filho, Oswaldo Julio; Corsato, Liatar Giorge; Quiessi, Jorge Aparecido; Kanno, Oscar Yoshikatsu; Penteado, Raul Barros; Arabori, Roberto Mikio; Belorte, Lucia Cristina Camargo; Lima, Márcio Emanoel de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to diagnose erosions in a hydrographic basin and to evaluate conservationist soil management practices for degradation recovery, by monitoring water quality indicators and satellite images. Monitoring was done for 14 years in 14,076 ha of the basin of Rio do Peixe, which was selected for being the most degraded one in the state of São Paulo, Brazil, circumscribing 176 farms, basically explored with pastures and coffee. Out of these farms, 82 showed some kind of erosion, besides 12 stretches of municipal roads that contributed to the erosion processes in the agricultural areas. The conservationist soil and water management practices established in 86 of the farms at the basin allow positive changes on the landscape and on the income from agricultural activity, which were shown in the aerial photos and by the water quality indicators. The adopted monitoring and agri-environmental rehabilitation methodologies are viable and may contribute to managing and monitoring microbasins.